Circular RNA circPSD3 alleviates hepatic fibrogenesis by regulating the miR-92b-3p/Smad7 axis - Fang-tian Bu; Yan Zhu; Xin Chen; Ao Wang; Ya-fei Zhang; Hong-mei You; Yang Yang; Ya-ru Yang; Cheng Huang; Jun Li (Elsevier, 2021)
Recently, circular RNAs (circRNAs) have been frequently reported to be involved in hepatocellular carcinoma (HCC) development and progression. However, the role of circRNAs in hepatic fibrosis (HF) is still unclear. Our previous high-throughput screen revealed changes in many circRNAs in mice with carbon tetrachloride (CCl4)-induced HF. For instance, the expression of circPSD3, a circRNA derived from the Pleckstrin and Sec7 domain-containing 3 (PSD3) gene, was considerably downregulated in primary hepatic stellate cells (HSCs) and liver tissues of mice with CCl4-induced HF compared to those in the vehicle group. In vivo overexpression of circPSD3 using AAV8-circPSD3 arrested the deterioration of CCl4-induced HF as indicated by reduced serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) content, liver hydroxyproline level, collagen deposition, and pro-fibrogenic gene and pro-inflammatory cytokine levels. Moreover, in vitro loss-of-function and gain-of-function analyses suggested that circPSD3 inhibited the activation and proliferation of HSCs. Mechanistically, circPSD3 served as a sponge for miR-92b-3p, subsequently promoting the expression of Smad7. In conclusion, our present findings reveal a novel mechanism by which circPSD3 alleviates hepatic fibrogenesis by targeting the miR-92b-3p/Smad7 axis, and they also indicate that circPSD3 may serve as a potential biomarker for HF.